Wakaf di Era Modern: Wakaf Saham di Pasar Modal Syariah (Studi pada MNC Sekuritas - Meidya Putri (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
: The development of science and technology has encouraged the emergence of new concepts and thoughts to introduce philanthropy in the form of zakat infaq and waqf through the Islamic Commercial System, especially in the Sharia capital market. The implementation of sharia share waqf has started in 2019 and involves IDX Islamic, Securities Companies and Philanthropic Institutions. On this basis, it is necessary to analyze the performance achievements of waqf assets from sharia shares that investors have distributed to waqf institutions. This research uses qualitative methods with data analysis through triangulation. The total assets of share waqf distributed by wakifs (Sharia investors) reached IDR 276,524,244 during 2021 and until December 2022, the value of share waqf reached IDR 285,900,654 with an increase of 3.39% or IDR 9,376,000. MNC Sekuritas has contributed 35% to the achievement of share waqf assets in the Indonesian sharia capital market and 90% of the number of wakifs recorded on IDX Islamic comes from MNC Sekuritas customers, namely 200 sharia investor customers. Sharia share waqf means waqf in the modern era where waqf funds come from the investment value of sharia shares owned by investors and are managed by nadzir through the capital market. The implication of this research is that it is hoped that the performance of waqf assets can be accompanied by an increase in the professionalism of nadzir in managing share waqf assets, which of course is related to nadzir's expertise in managing sharia stock portfolios (waqf assets) in the sharia capital market